Pathogenesis of neonatal asphyxia - Dr. Rabindran; D. Sharad Gedam (Tropical Journal of Pathology and Microbiology, 1970)
Asphyxia results from compromised gas exchange. Pathogenesis of neonatal asphyxia involves energy crisis, lactic acidosis, excitotoxicity& free radical injury. Initial poor oxygenation leads to hypoxemia with intact organ function.Later hypoxia develops with anaerobic metabolism followed by asphyxia with involvement of major organs. The changes during asphyxia depend on organ involvement & its severity. Interference with cerebral blood flow secondary to systemic hypotension leads to failure of cerebral autoregulation thereby leading to ischemia, neuronal &oligodendoglial damage via excitoxicity. Reduced oxygen supply leads to ineffective oxidative phosphorylation, anaerobic metabolism & depletion of ATP reserves, accumulation of lactic acid & hydrogen ions & reduced cellular functions. ATP-dependent sodium-potassium pump fail leading to disruption of ion exchange across cell membrane leading to cell injury. Types of hypoxic brain damage include Haemorrhagic lesions, Destructive lesions involving white matter & grey matter. Neuropathological patterns of injury include Selective neuronal necrosis, White matter lesions, Combined lesions & Advanced lesions including Ulegyria, Multifocal cystic encephalopathy, Status marmaratus&Unifocalpseudocyst. Brain ischemia, inflammation & neuronal cell death are the 3 major steps in the pathogenesis of neural damage during asphyxia. Brain histology helps in timing of asphyxia which depend on aetiology & stage of neurodevelopment.Reperfusion temporarily corrects this energy failure, however it may trigger delayed neuronal death or secondary damage due to brain swelling. Ischemia & reperfusion induce both rapid & delayed changes in gene expression. Asphyxia negatively affects integrity of the genome, triggering activation of sentinel proteins that maintain genome integrity.